Distribution of the temperature in friction stir welding of aluminum and copper alloys - Rzaev Radmir; Sundetov Marat; Valisheva Alfiya; Derzhavin Igor; Merkulov Denis (E3S Web of Conferences, 2023)
Friction stir welded are studied joints of pure copper M1 and aluminum alloy AD1. A technique for measuring the temperature was developed at the points of the weld. The results of measurement temperature are given in friction stir welding at various speeds of rotation of the welding tool (800-1000 rpm), welding speed (25-61 mm/min). The temperature reached in copper is about 60 K higher than in aluminum. The higher cooling rate of copper is due to the greater thermal diffusivity than that of aluminum. The maximum temperature in the copper reached 769 K, which was lower than the melting point of the eutectic in the Al-Cu system (821 K). The residence time above the temperature of formation of intermetallic compounds (623 K) is much shorter than the duration of the thermal cycle (50 s). With an increase in the welding tool rotation frequency from 800 to 1000 rpm, the maximum temperature near the pin increases from 650 to 769 K. At a tool rotation frequency of 800 rpm, the maximum temperature in copper achieved in the cycle is lower than the transition temperature to the superplastic state and is 764 K high heating and free cooling rates (50–145 K/s and 25–50 K/s) of the weld on the side of the copper alloy predetermine the short-term (from 5 to 15 s) stay of the metal in the temperature range of formation of intermetallic phases.